Pengaruh Pendapatan Asli Daerah, Dana Perimbangan, Dan Belanja Modal Terhadap Kinerja Keuangan (Studi Kasus pada Pemerintah Kabupaten Bandung Barat) - Rahardjo, Bianca; Sutrisno Putra, Sugih (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
How well local governments manage regional budgets is reflected in how well those governments operate financially. The purpose of this research is to analyze the relationship between local governments' financial health and their original income, equalization fund, and capital expenditure. The West Bandung Regency served as the study's primary location. Saturated sampling methods were employed in this research, and both documentary data and subject data were documented for analysis. Secondary information from the BPK RI-audited West Bandung Regency Budget Realization Report was utilized for this analysis. Data is gathered via document studies and interviews conducted by non-observers, and multiple linear regression is employed for analysis. Multiple linear regression analysis indicated that the financial performance of local governments was significantly affected positively by local original income and The Balancing Fund and negatively by Capital expenditure.